QUALITY OF WORK LIFE OF PERSONNAL IN DIRECTORATE OF QUARTERMASTER ROYAL THAI AIR FORCE - Mangmee, Akaradej; Niphitprasart Soonthornvipart, Lalita; Klaitabtim, Juthathip (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
The objectives of this research were 1) to study the quality of work life of personnel in Directorate of Quartermaster Royal Thai Air Force, 2) to study the organizational climate and organizational culture factors of personnel in Directorate of Quartermaster Royal Thai Air Force, 3) to compare the quality of work life of personnel in Directorate of Quartermaster Royal Thai Air Force, classified by personnel factors, 4) to study the relationship between organizational climate, organizational culture and the quality of work life of personnel in Directorate of Quartermaster Royal Thai Air Force and 5) to study the relationship between organizational and the quality of work life of personnel in Directorate of Quartermaster Royal Thai Air Force. The sample group used in this research was 211 persons of Directorate of Quartermaster Royal Thai Air Force. The instrument used for data collection was a questionnaire, Index of item – Objective Congruence is between 0.80 – 1.00 with Cronbach's confidence coefficient of 0.92 and the statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test value, One-Way ANOVA, and Pearson’s correlation coefficient with a statistical significance of 0.05. The results of the research found that 1) the personnel in Directorate of Quartermaster Royal Thai Air Force had overall quality of work life at a high level, 2) the organizational climate and organizational culture factors were related to the quality of work life of the Royal Thai Air Force personnel statistically significant at the 0.05 level and 3) personal factors, including marital status, rank, and job position were different. There is no difference in quality of working life. While personnel with age, education level, salary rate and the duration of operation is different have different quality of working life was statistically significant at the 0.05 level.